Long-term follow-up and health-related quality of life in COVID-19 patients treated in hospital - Gunluoglu, Gulsah; Cortuk, Mustafa; Veske, Nurdan Simsek; Cinarka , Halit; Atasever, Furkan; Arslan, Melih Akay (Journal of the Pakistan Medical Association, 2022)
Objective: To evaluate the persistence of symptoms and health-related quality of life of coronavirus disease-2019 patients. Method: The cross-sectional study was conducted from April to September 2020 at Health Sciences University, Yedikule Chest Hospital, Istanbul, Turkey, and comprised patients of either gender who had to be hospitalised and treated for coronavirus disease-2019. Those who had spent 3 months (46-90 days) post-discharge formed Group 1, those having spent 3-6 were in Group 2, while those with >6 months post-discharge were in Group 3. Data was collected over the telephone Using the European Quality of Life Scale with 5 dimensions and 5 levels. The variables likely to affect the persistence of symptoms and the quality of life questionnaire scores were analysed using SPSS 16. Results: Of the 225 subjects, 135(60%) were male and 90(40%) were female. The overall mean age was 55.7+/-19.91 years. There were 85(37.8%) participants in Group 1, 83(36.9%) in Group 2, and 57(25.3%) in Group 3. The age (p=0.09) and gender (p=0.23) distribution across the groups had no significant difference. Patients were called on an average 131.72+/-58.9 days after discharge (range: 46-279 days). Only 23.1% patients continued to show symptoms. Anxiety was the domain in which most patients 64(28.4%) reported deterioration. Conclusion: Most patients who have had coronavirus disease-2019COVID-19 after a long follow-up period did not show any symptoms or had any significant deterioration in their quality of life. Key Words: COVID 19, Post-discharge symptoms, Quality of life.